Genetic and environmental control of fruit maturation, dry matter and firmness in apple (Malus × domestica Borkh.). (17th September 2014) - Chagné, David; Dayatilake, Daya; Diack, Robert; Oliver, Murray; Ireland, Hilary; Watson, Amy; Gardiner, Susan E; Johnston, Jason W; Schaffer, Robert J; Tustin, Stuart
Abstract: For any given genotype, the environment in which an apple is grown can influence the properties of the fruit considerably. While there has been extensive research on the mechanism of the genetic control of fruit quality traits, less effort has been made to investigate the way that these genetic mechanisms interact with the environment. To address this issue, we employed a large 'Royal Gala' × 'Braeburn' population of 572 seedlings replicated over sites in three climatically diverse apple-growing regions in New Zealand. Phenotyping for traits including fruit maturation timing, firmness and dry matter content was performed at each of these three sites for a single growing season (2011), and at two sites (Motueka and Hawke's Bay) for two seasons (2009 and 2010). The phenotype data collected over 2 years at two sites enabled the detection of 190 quantitative trait loci (QTL) that controlled these traits regardless of year or growing location, as well as some chromosomal loci that influenced the traits in a single given environment or year. For those loci that were environmentally stable over three sites, there was an interdependency of fruit maturation date, dry matter content and storage potential within this population, with two regions on Linkage Groups (LGs) 10 and 16 strongly contributing. If these loci were used in a marker-assisted selection programme to select for progeny bearing firmer fruit, this would have the unintentional consequence of selecting, high dry matter content, later maturing apples. In addition, a further 113 new QTLs with a smaller effect were identified, some of which were exhibited only in a single growing environment, demonstrating the underlying complexity of control of traits determining fruit quality, in addition to the need for being aware of environmental effects when developing new apple varieties. Fruit crops: Genes and environment influence apple quality: The interaction between the effects of genes and environment on the texture and storage properties of apples is explored in a new study. The desirability of an apple depends greatly on its texture, a complex trait determined by both genetic and environmental factors. David Chagné and colleagues at the New Zealand Institute for Plant & Food Research studied nearly 600 trees at three climatically different sites over three years. They identified 190 quantitative trait loci (QTLs), genome regions controlling complex traits, influencing fruit maturation, firmness and storage potential. Unusually, many of these were "small effect" QTLs. QTLs with large effects tended to act similarly at all sites. However, some plants with small effect QTLs were strongly affected by environment and others more resistant. These could be used to breed apple cultivars suited to diverse conditions.